Credit Performance and BOPO Ratio at Banks in Indonesia Before and During Covid-19 - Eka Putra, Wirmie; Safelia, Nela; Ibrahim, Azzahra Adira (Faculty of Economics and Business Universitas Jambi, 2024)
The purpose of this study is to look the differences in credit performance and BOPO ratio in Conventional and Islamic banks in Indonesia before and during Covid-19. This comparison is done by using NPL/NPF and BOPO ratio variables. The population in this study were all Conventional and Islamic banks in Indonesia, while 92 samples were selected for conventional banks and 14 samples for Islamic banks using purposive sampling technique with several criteria. The research data is in the form of secondary data sourced from the March 2019 – December 2020 quarterly report which are supported by data from OJK. The research analysis tool using the wilcoxon test. The results of the research that have been carried out show that NPL and BOPO at Conventional Banks show differences between before and during Covid-19, while NPF and BOPO at Islamic Banks before and during Covid-19 remain. According to this study, Indonesian conventional banks saw changes in their credit risk (NPL) and efficiency (BOPO) during COVID-19, but Islamic banks saw little change. This should, in theory, strengthen Islamic banking models' ability to withstand crises. In practice, it implies that Islamic banks should keep concentrating on operational effectiveness while conventional banks require more robust risk management during economic downturns.